The rise of foreign banks in China - Zhang, Shenli (2007)
Since the economy reform, its fragile banking sector may turn out to the single biggest threat to China's macroeconomic stability and long-term growth. Foreign financial investors have been introduced to help Chinese government to reform its financial systems. At the same time, foreign investors have their own considerations to enter into Chinese market. With the purposes to balance their interests, proper entry approaches and entry strategies will be discussed